Effects of dietary bixin on broiler performance and meat quality - Luiggi, Fabiana Golin [UNESP]; Pacheco, Peterson Dante Gavasso [UNESP]; Racanicci, Aline Mondini Calil; de Souza Miranda Muynarsk, Elisângela [UNESP]; Fasanaro, Ricardo [UNESP]; Sartori, José Roberto [UNESP] (Universidade Federal do Paraná, 2020)
Bixin is the main carotenoid present in annatto seed (Bixa orellana). The aim of this study was to evaluate the inclusion of increasing levels of bixin in the broiler diets and their effects on growth performance and meat characteristics. A total of 750 one-day-old Cobb 500 chicks were distributed in a completely randomized design with five treatments, with six replications of twenty-five birds each. Treatments consisted in different levels of bixin in diets (0.0, 0.05, 0.10, 0.15%). Were evaluated the parameters of growth performance (weight gain-WG, feed intake-FI, feed conversion ratio-FCR, productive efficiency index-PEI and viability), meat quality (pH, color, drip loss, cooking loss-CL and shear force-SF), cholesterol levels and meat oxidation. The inclusion of 0.25% of bixin resulted in negative effect on WG and PEI. The values of b * (intensity of yellow) increased linearly with the inclusion of bixin. The addition of 0.10% bixin in diet reduced the cooking loss and the addition of 0.15% reduced the shear force. The inclusion of 0.25% of bixin in diet had an antioxidant effect on breast and thigh meat, 10 days after cooking. The addition of bixin in broilers diet did not affect performance and had positive effects on meat quality, in parameters that directly affect the consumer's purchase decision.
Uso de bixina na dieta de frangos de corte e seus efeitos no desempenho zootécnico e qualidade da carne
Keywords: Additive; Annatto extract; Cholesterol; Natural antioxidant